ANALYSIS OF CONSTRUCTIVIST THEORY IN STUDENT-CENTERED LEARNING TO IMPROVE ACTIVE PARTICIPATION IN COSMETOLOGY, ETHNOBEAUTY, AND WELLNESS EDUCATION IN INDONESIA - Amelia Nur Zahira; M.Mamduh Winangun; Sri Usodoningtyas (Universitas Negeri Surabaya, 2026)
This article aims to analyze the application of constructivist theory in student-centered learning as an effort to address the low level of active student participation in Indonesia, with specific relevance to cosmetology, ethnobeauty, and wellness education. Educational problems in Indonesia are reflected in low learning outcomes, limited length of schooling, and the dominance of lecture-based methods that position students as passive recipients of information. Constructivist theory emphasizes that students construct knowledge through experience, interaction, reflection, and active engagement with their learning environment. This article uses a qualitative method with a literature study approach. The analysis indicates that low active participation is related to the limited application of active learning principles that are aligned with constructivism. In the context of beauty and wellness education, student-centered learning is important because students need to develop not only conceptual understanding, but also practical skills, cultural awareness, creativity, client-centered communication, and responsible attitudes toward traditional and sustainable beauty practices. Therefore, the implementation of discussion, inquiry, project-based learning, collaborative practice, and reflective activities can strengthen student participation and support meaningful learning. The shift from teacher-centered to student-centered learning is expected to improve the quality of education by developing students who are cognitively active, technically competent, culturally aware, and professionally prepared for the beauty and wellness field.